2024
DOI: 10.1039/d3cs00717k
|View full text |Cite
|
Sign up to set email alerts
|

Metal nitrides for seawater electrolysis

Huashuai Hu,
Xiaoli Wang,
J. Paul Attfield
et al.

Abstract: The current strategies and basic mechanisms of metal nitrides for hydrogen production from seawater are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 283 publications
(408 reference statements)
0
10
0
Order By: Relevance
“…Metal atoms, including transition metals (TMs), incorporated into nitrogen cluster nanoparticles are recognized as potential high-energy-density materials due to substantial energies released during the fragmentation reactions. 1–6 Compared to pure nitrogen clusters, which suffer from poor stabilization and challenging preparation processes, metal-doped nitrogen clusters exhibit distinctive properties. Normally, the nitrogen skeletons are prone to enhance their stabilities through bonding with the metal atoms and their structures show diversity, making them environmentally friendly high-energy-density material candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Metal atoms, including transition metals (TMs), incorporated into nitrogen cluster nanoparticles are recognized as potential high-energy-density materials due to substantial energies released during the fragmentation reactions. 1–6 Compared to pure nitrogen clusters, which suffer from poor stabilization and challenging preparation processes, metal-doped nitrogen clusters exhibit distinctive properties. Normally, the nitrogen skeletons are prone to enhance their stabilities through bonding with the metal atoms and their structures show diversity, making them environmentally friendly high-energy-density material candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Electrolytic water splitting, as a next-generation renewable energy conversion device, has been widely recognized as a more promising and sustainable technology to produce carbon emission-free green hydrogen, compared to other hydrogen production methods. Proton exchange membrane water electrolysis (PEMWE) is highly desirable due to its advantages of fewer unfavorable reactions, lower resistance losses, and faster system response, compared to alkaline water electrolysis. The fast response feature endows its continuous hydrogen production by using intermittent power sources from wind energy, solar energy, etc. Unfortunately, most OER electrocatalysts suffer from severe degradation in PEMWE due to high voltage and acidic environments. Thus, it is a major challenge to design acidic OER catalysts with long-term stability and high activity to meet the requirements in PEMWE.…”
Section: Introductionmentioning
confidence: 99%
“…Electrolytic hydrogen production from seawater offers an economical, sustainable, and efficient strategy for renewable hydrogen generation [1][2][3][4][5]. However, the abundant presence of Cl − ions in seawater poses a challenge to the anodic catalysts [6][7][8][9][10]. Effective and sustainable seawater electrolysis requires highly active and stable anodic catalysts capable of maintaining an overpotential for the oxygen evolution reaction (OER) consistently below 480 mV to prevent chloride oxidation reactions (CIORs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Effective and sustainable seawater electrolysis requires highly active and stable anodic catalysts capable of maintaining an overpotential for the oxygen evolution reaction (OER) consistently below 480 mV to prevent chloride oxidation reactions (CIORs) [11]. Previous studies have shown that Ni-, Co-, and Fe-based phosphides [12], sulfides [2,13,14], selenides [15], nitrides [6,16], and hydroxides [17][18][19][20] exhibit excellent stability in seawater environments, but their activity needs further enhancement.…”
Section: Introductionmentioning
confidence: 99%